2021
DOI: 10.3390/pr9081370
|View full text |Cite
|
Sign up to set email alerts
|

Anticancer Properties of Strobilanthes crispus: A Review

Abstract: Cancer is a major cause of death worldwide, as exemplified by millions of cancer diagnoses every year. The use of chemotherapy in treating cancer has many disadvantages which include recurrence of cancer, associated with drug resistance, and severe side effects that are harmful to the patients. A better source of anticancer drugs can come from nature. Strobilanthes crispus (S. crispus) is a herbal medicinal plant that is indigenous in Madagascar and the Malay Archipelago. The plant possesses high vitamin and m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 69 publications
0
3
0
1
Order By: Relevance
“…Strobilanthes crispus leaves are grown in Malaysia for their usage in the pharmaceutical sector as a product that promotes health and for its traditional use as a diuretic, a blood thinner, and a treatment of cancer [ 31 ]. According to recent studies, the medicinal chemicals in the leaves may be a source of anticarcinogens and are, therefore, utilized as chemotherapeutic agents to treat cancer [ 32 ].
FIGURE 6 Diplazium esculentum (Retz.)
…”
Section: Resultsmentioning
confidence: 99%
“…Strobilanthes crispus leaves are grown in Malaysia for their usage in the pharmaceutical sector as a product that promotes health and for its traditional use as a diuretic, a blood thinner, and a treatment of cancer [ 31 ]. According to recent studies, the medicinal chemicals in the leaves may be a source of anticarcinogens and are, therefore, utilized as chemotherapeutic agents to treat cancer [ 32 ].
FIGURE 6 Diplazium esculentum (Retz.)
…”
Section: Resultsmentioning
confidence: 99%
“…The results of in vitro xanthine oxidase inhibition assay of some selected gout medicinal plants from Indonesia was summarized in The Strobilanthes crispa L. Blume leaves, known as keji beling in Indonesia, have been reported to have many pharmacological activities, including as anti-hyperglycemic, anti-oxidant, antimicrobial, wound healing anti-cancer on breast, liver cervical, lung, prostate and nasopharyngeal cancer, anti-inflamatory, antitrypanosomal, anti-obesity [31][32][33][34][35][36][37]. However, the research on the Strobilanthes crispa L. Blume leaves as an anti-hyperuricemia has never been studied before, thus, it in necessary to do further research regarding the potential of this plant to be a gout medicine.…”
Section: Resultsmentioning
confidence: 99%
“…HLA is expressed with specific promoter proteins such as CIITA (Carey et al 2019 ). The rise in the IFN-γ is accompanied by the upregulation of CIITA expression which in turn promoted the expression of MHC-II molecules that are responsible for the binding of CD4 + T cells (Ng et al 2021 ). Data revealed that flavonoids inhibit antigen-specific memory T cell proliferation and pro-inflammatory IFN-γ production (Verbeek et al 2005 ).…”
Section: Discussionmentioning
confidence: 99%